2021
DOI: 10.1038/s41598-021-02496-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimate change in the Garhwal Himalaya, India at 4200 yr BP coincident with the contraction of the Indus civilization

Abstract: High-resolution analysis of a 3.80 m sediment core recovered from Deoria Tal, a mid-elevation lake located at 2393 m a.s.l. in the Garhwal Himalaya, documents long-term and abrupt hydroclimate fluctuations in northern India during the mid- to late Holocene. The sediment chronology, based on ten 14C dates, indicates the core spans 5200 years. Non-destructive, radiological imaging approaches (X-ray fluorescence (XRF), X-ray imaging, and CT scans) were used to assess the response of the lake system to changing hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
(142 reference statements)
0
5
0
1
Order By: Relevance
“…Mo has a limit of detection of <5 ppm and Ti <25 ppm. A handheld XRF method for determining elemental concentrations in lacustrine sediments is a commonly used, rapid method (e.g., Niederman et al, 2021; Wright et al, 2023). However, the data should be considered semi-quantitative due to inherent sediment heterogeneity and its variable clastic, organic, and chemical components (Weltje and Tjallingii, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Mo has a limit of detection of <5 ppm and Ti <25 ppm. A handheld XRF method for determining elemental concentrations in lacustrine sediments is a commonly used, rapid method (e.g., Niederman et al, 2021; Wright et al, 2023). However, the data should be considered semi-quantitative due to inherent sediment heterogeneity and its variable clastic, organic, and chemical components (Weltje and Tjallingii, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Further, an unstable trend of strengthening occurred until ~1.5 cal kyrs BP, followed by a weakening monsoon that intensified at 0.8 cal kyrs BP. Niederman et al (2021) also reported episodes of dry events at 4.8, 4.2, and 3.1 cal kyrs BP based on multi-proxy analysis of sediment core retrieved from Deoria Tal. Contradicting this, Bhushan et al (2018) reported periods of enhanced monsoon at 5–4.2, 3.5–2.4, and 1.8–1 cal kyrs BP, respectively with relatively cold and dry periods occurring at 5.8–3.7 and 2.1–0.69 cal kyrs BP.…”
Section: Introductionmentioning
confidence: 93%
“…Tso Moriri (Mishra et al, 2015); 14. Deoria Tal (Niederman et al, 2021); 15. Manasbal Lake (Babeesh et al, 2019); 16.…”
Section: Present Climateunclassified
“…Nile flow is a function of seasonal Indian Summer Monsoon (ISM) precipitation over the Ethiopian highlands that provides an average 80% of the Lake Tana sources of the Blue Nile and Tekeze-Atbara Rivers measured by air mass back trajectories, which then provide 90% of Nile flow ( 11 13 ). The proximate cause of the abrupt ~4.2 ka BP Nile flow reduction was the ISM megadroughts at 4.2 ka BP to 4.17 ka BP, 4.14 ka BP to 4.08 ka BP, and 4.06 ka BP to 3.97 ka BP, now measured to subdecadal and seasonal resolution in Indus speleothem, marine ( 14 , 15 ), and lake cores ( 16 ).…”
Section: Old Kingdom Collapsementioning
confidence: 99%